DIGITAL TRANSFORMATION, INSTITUTIONAL QUALITY, AND SME INCOME INEQUALITY IN SOUTHEAST ASIA - Muhammad Arafah (GREET, 2026)
This study examines the dynamic relationship between digital transformation, institutional quality, and income inequality among small and medium-sized enterprises (SMEs) in Southeast Asia, addressing a critical gap in understanding the distributional effects of digitalization in emerging economies. While digital transformation is widely recognized as a driver of productivity, innovation, and market expansion, its benefits are often unevenly distributed due to structural and institutional disparities. Employing a mixed-methods approach, this research integrates quantitative data from 1,200 SMEs across Indonesia, Malaysia, and Vietnam with qualitative insights from semi-structured interviews involving key stakeholders, enabling both empirical testing and contextual interpretation. The findings reveal that digital transformation significantly increases SME income and resilience, with digitally adopting firms experiencing up to 30% higher income growth compared to non-adopters. However, this positive effect is strongly conditioned by institutional quality, measured through governance effectiveness, regulatory frameworks, and access to finance. SMEs operating in countries with stronger institutional environments benefit disproportionately from digitalization, while those in weaker institutional contexts face structural barriers that exacerbate income inequality. The study further identifies a persistent digital divide across firm size, sector, and geographic location, reinforcing a “digital Kuznets curve” dynamic in which early adopters capture disproportionate gains. Critically, the results suggest that digital transformation alone is insufficient to ensure inclusive growth; rather, it must be complemented by institutional strengthening to mitigate inequality. This research contributes to the literature by integrating institutional economics with digital transformation theory and offers policy-relevant insights, emphasizing the need for coordinated strategies that enhance digital access, improve governance quality, and support equitable SME development in Southeast Asia.